2016
DOI: 10.1186/s41476-016-0017-5
|View full text |Cite
|
Sign up to set email alerts
|

A single mode porous-core square lattice photonic crystal fiber for THz wave propagation

Abstract: Background: Interests on low-loss terahertz (THz) waveguides are increasing due to their remarkable applications in various fields. Since most the materials are highly absorbent to THz waves therefore it is an ongoing challenge to obtain a low-loss waveguide. This paper presents a novel porous-core square lattice photonic crystal fiber (PCF) for efficient transmission of THz waves. Methods: The guiding properties of the proposed fiber are characterized by using finite element method (FEM) with circular perfect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…The wave propagation in porous‐core MOF is mainly limited by the EML, which can be computed by the following expression [11, 12]: αeff=)(ε0/μ01/2Amatnαmat||E2normaldnormalA2AllSzdA, where ɛ 0 and µ 0 are the permittivity and permeability in vacuum, n is the refractive index of TOPAS, E is the electric field component, and S z is the z‐component of the Poynting vector.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wave propagation in porous‐core MOF is mainly limited by the EML, which can be computed by the following expression [11, 12]: αeff=)(ε0/μ01/2Amatnαmat||E2normaldnormalA2AllSzdA, where ɛ 0 and µ 0 are the permittivity and permeability in vacuum, n is the refractive index of TOPAS, E is the electric field component, and S z is the z‐component of the Poynting vector.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…Another porous‐core MOF was reported by Chen et al [10] having an EML of 0.1 cm −1 and a confinement loss of 1.7 dB/cm at 1.0 THz. The MOF demonstrated in [11] showed a low EML of 0.076 cm −1 and a low confinement loss of 8.96 × 10 −3 dB/cm at 1.0 THz. Besides, a porous‐core spiral MOF has been proposed by the authors, which showed a low EML of 0.085 cm −1 and a low confinement loss of about 1.91 × 10 −3 dB/cm at 1.0 THz [12].…”
Section: Introductionmentioning
confidence: 99%
“…Zeonor is used as the background material of the reported RH-CPCF sensor. To compare with recent published articles [22][23][24][25][26][27][28][29][30][31][32][33][34], the proposed RH-CPCF shows the better performance of sensitivity and confinement loss are 76.44%, 77.16%, 73.20% and 2.33 × 10 −03 dB/m, 3.07 × 10 −06 dB/m, 2.84 × 10 −02 dB/m for ethanol, benzene and water respectively at 1 THz frequency. So, this suggested RH-CPCF is highly useful in biomedicine and industrial chemicals research for sensing applications in the terahertz frequency range.…”
Section: Introductionmentioning
confidence: 85%
“…In 2014, Rana et al [15] suggested octagonal lattice PCF and gained EML of 0.05 cm −1 and core power of 40% at 1 THz. In 2016, Hasan et al [16,17] reported hexagonal and square lattice PCFs which gained EML of 0.089 cm −1 and 0.076 cm −1 , respectively. However, core power fraction was very low and did not mention some crucial parameters.…”
Section: Introductionmentioning
confidence: 99%